2023
DOI: 10.1111/jne.13268
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic corticotrophin releasing hormone neurons in stress‐induced psychopathology: Revaluation of synaptic contributions

Abstract: Stress has a strong influence on mental health around the world. Decades of research has sought to identify mechanisms through which stress contributes to psychiatric disorders such as depression, to potentially guide the development of therapeutics targeting stress systems. The hypothalamic pituitary adrenal (HPA) axis is the key endocrine system that is responsible for coordinating body-wide changes that are necessary for survival under stress, and much of the research aimed at understanding the mechanisms b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 128 publications
0
3
0
Order By: Relevance
“…Repeated daily cat exposure ( 41 ), CVS ( 47 49 ) and repeated immobilization ( 50 ) up-regulated PVN mRNA CRH expression in the rat. It has also been demonstrated that PVN neurons remain active after long-term glucocorticoid negative feedback ( 51 ), and chronic stress may even increase the excitability of PVN CRH neurons via multiple mechanisms ( 52 ). Our mathematical modeling could also be extended to interrogate other physiological phenomena such as the mechanisms by which the PVN CRH neural system underlies the adverse outcomes of nutritional programming on cardiovascular disease ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Repeated daily cat exposure ( 41 ), CVS ( 47 49 ) and repeated immobilization ( 50 ) up-regulated PVN mRNA CRH expression in the rat. It has also been demonstrated that PVN neurons remain active after long-term glucocorticoid negative feedback ( 51 ), and chronic stress may even increase the excitability of PVN CRH neurons via multiple mechanisms ( 52 ). Our mathematical modeling could also be extended to interrogate other physiological phenomena such as the mechanisms by which the PVN CRH neural system underlies the adverse outcomes of nutritional programming on cardiovascular disease ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, secreted GCs from the adrenal glands, located on top of the kidneys, contribute to regulated blood levels of GCs via the negative feedback mechanism of the HPA axis. Since the HPA axis is considered a key endocrine system that has a critical role in the coordination of body-wide changes to survive stress, a lot of studies are focusing on the relationship between depression and the dysfunction of the HPA axis [22]. Recent evidence also shows changed neuronal function of corticotrophin-releasing hormone (CRH) neurons in the paraventricular nucleus of the hypothalamus (PVN) is involved in stress-related behaviors [22].…”
Section: Glucocorticoids and Neuronal Functionsmentioning
confidence: 99%
“…Since the HPA axis is considered a key endocrine system that has a critical role in the coordination of body-wide changes to survive stress, a lot of studies are focusing on the relationship between depression and the dysfunction of the HPA axis [22]. Recent evidence also shows changed neuronal function of corticotrophin-releasing hormone (CRH) neurons in the paraventricular nucleus of the hypothalamus (PVN) is involved in stress-related behaviors [22]. Generally, an activation of the HPA axis, which is required for the secretion of GCs acting on a variety of organs to cope with stress during the process of adaptation, invokes CRH release from PVN neurons.…”
Section: Glucocorticoids and Neuronal Functionsmentioning
confidence: 99%